2018
DOI: 10.1111/1471-0528.15396
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐initiated follow up affects fear of recurrence and healthcare use: a randomised trial in early‐stage endometrial cancer

Abstract: Why and how was the study carried out? Follow up of women with endometrial cancer is resource consuming and previous research suggests that it is not effective. Even though the women benefit from reassurance at follow up, routine examinations may also remind the women of the disease and induce fear of cancer recurrence. Furthermore, routine follow up may delay recurrence diagnosis, because the women do not report their symptoms until the next scheduled visit. In the research explained in this article, patient-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 28 publications
0
74
0
Order By: Relevance
“…These are important findings, as a wide host of studies have noted that the recurrence of endometrial and ovarian cancers is often symptomatic, with figures for endometrial cancer ranging from TA B L E 2 Questionnaires and symptom checklist data at 0-2, 2-5 and >5 years after treatment completion TA B L E 3 Anxiety as categorical data at 0-2, 2-5 and >5 years after treatment completion 40% to 91% (Fung- Kee-Fung et al, 2006;Sartori et al, 2010). Yet is noteworthy to remember that a proportion of recurrences were reported as interval events and detected in between FU (Jeppesen et al, 2017), highlighting the need for an accessible on-demand channel such as patient-initiated FU (Jeppesen, Jensen, Hansen, Christensen, & Mogensen, 2018;Kumarakulasingam et al, 2019) through which symptoms may be reported on view to increase the detection and facilitate swifter management of recurrent disease.…”
Section: Discussionmentioning
confidence: 99%
“…These are important findings, as a wide host of studies have noted that the recurrence of endometrial and ovarian cancers is often symptomatic, with figures for endometrial cancer ranging from TA B L E 2 Questionnaires and symptom checklist data at 0-2, 2-5 and >5 years after treatment completion TA B L E 3 Anxiety as categorical data at 0-2, 2-5 and >5 years after treatment completion 40% to 91% (Fung- Kee-Fung et al, 2006;Sartori et al, 2010). Yet is noteworthy to remember that a proportion of recurrences were reported as interval events and detected in between FU (Jeppesen et al, 2017), highlighting the need for an accessible on-demand channel such as patient-initiated FU (Jeppesen, Jensen, Hansen, Christensen, & Mogensen, 2018;Kumarakulasingam et al, 2019) through which symptoms may be reported on view to increase the detection and facilitate swifter management of recurrent disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recent UK study has reported that PIFU is well received by women treated for endometrial cancer, although younger women (median age 57 years) initiated more contact with health care staff, indicating they needed a higher level of support (Kumarakulasingam et al, 2019). A study carried out in Denmark reported that PIFU for endometrial cancer patients (n = 156) was feasible and potentially cost effective but patients in the PIFU arm indicated significantly higher levels of fear of recurrence than in the hospital follow-up arm of the study (reported difference of −5.9; 95% CI -10.9 to −0.9, p = 0.02) (Jeppesen et al, 2018). It was speculated that the increased responsibly put on women to detect signs of recurrence may have increased levels of stress (Jeppesen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is very important that patients are given written information about PIFU, which includes the contact details should they need them. Most patients find PIFU acceptable 17 , although younger patients and those who struggle to access healthcare (due to socio-demographic factors) may require the additional support 18 Although there was no patient representative at the BGCS PIFU meeting, there has been positive feedback from patients within the hospitals that have already implemented the guidelines and in studies that looked at patient acceptability [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%